A Descriptive Survey to Assess the Knowledge of Multi Purpose Health Workers and Problems Encountered by them in the Management of Cold Chain System for Vaccines in Universal Immunization Programme in Selected Health Centres of NCR (U.P.) (International Journal of Nursing Education, 2019)
A descriptive survey to assess the knowledge of Multi Purpose Health Workers and problems encountered by them in the management of cold chain system for vaccines in Universal Immunization Programme in selected Health centres of NCR (UP).Objectives:1)To assess the knowledge of MPHW in management of cold chain system for vaccines in Universal Immunization Programme.2)To find out problems encountered by MPHW in management of cold chain system for vaccine in Universal Immunization Programme.3) To determine the association between knowledge about management of cold chain system with selected demographic factors. The conceptual framework developed for the study was based on the “Ludwig Open System Model”. The research approach for the study was descriptive survey approach; the study design was descriptive design. Non-Probability Purposive sampling Technique was used to obtain an adequate size of sample. The sample consisted of 100 MPHW’s working in Loni and Bisrakh Health Centres. Findings showed that: Majority of MPHW’s had the average knowledge 55(55%), 42(42%) had good knowledge and 1(1%) had poor knowledge regarding maintenance of Cold Chain system. Major Problems encountered by the MPHW’s were 72(72%) faced electricity problem, 71(71%) lack of availability of thermometer in recording the temperature of ILR, and 67(67%) faced difficulties in transporting the vaccines. Chi square value computed between knowledge score and selected demographic factors showed that the association of knowledge score of the MPHW’s with the Work Experience and In-Service training was found to be statically significant at 0.05 level of significance. It can be inferred that the knowledge of MPHW’s were dependent on their Work Experience and In-Service training. The study also discussed the implications of findings in the field of nursing education, practice, administration, research and for the society. The study concluded that the MPHW’s were having average knowledge regarding maintenance of cold chain system.
Keywords: MPHW, UIP, Problems. Cold Chain, Immunization, Management, Knowledge.